Development and assessment of an active strategy for the implementation of a collaborative care approach for depression in primary care (the INDI·i project) - Enric Aragonès; Diego Palao; Germán López-Cortacans; Antonia Caballero; Narcís Cardoner; Pilar Casaus; Myriam Cavero; José Antonio Monreal; Víctor Pérez-Sola; Miquel Cirera; Maite Loren; Eva Bellerino; et al. (BMC, 2017)
Abstract Background Primary care is the principal clinical setting for the management of depression. However, significant shortcomings have been detected in its diagnosis and clinical management, as well as in patient outcomes. We developed the INDI collaborative care model to improve the management of depression in primary care. This intervention has been favorably evaluated in terms of clinical efficacy and cost-effectiveness in a clinical trial. Our aim is to bring this intervention from the scientific context into clinical practice. Methods Objective: To test for the feasibility and impact of a strategy for implementing the INDI model for depression in primary care. Design: A quasi-experiment conducted in primary care. Several areas will be established to implement the new program and other, comparable areas will serve as control group. The study constitutes the preliminary phase preceding generalization of the model in the Catalan public healthcare system. Participants: The target population of the intervention are patients with major depression. The implementation strategy will also involve healthcare professionals, primary care centers, as well as management departments and the healthcare organization itself in the geographical areas where the study will be conducted: Camp de Tarragona and Vallès Occidental (Catalonia). Intervention: The INDI model is a program for improving the management of depression involving clinical, instructional, and organizational interventions including the participation of nurses as care managers, the efficacy and efficiency of which has been proven in a clinical trial. We will design an active implementation strategy for this model based on the PARIHS (Promoting Action on Research Implementation in Health Services) framework. Measures: Qualitative and quantitative measures will be used to evaluate variables related to the successful implementation of the model: acceptability, utility, penetration, sustainability, and clinical impact. Discussion This project tests the transferability of a healthcare intervention supported by scientific research to clinical practice. If implementation is successful in this experimental phase, we will use the information and experience obtained to propose and plan the generalization of the INDI model for depression in the Catalan healthcare system. We expect the program to benefit patients, the healthcare system, and society. Trial registration ClinicalTrials.gov identifier: NCT03285659 ; Registered 12th September, 2017.